2008
DOI: 10.1007/s12272-001-1155-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of DAAS derivatives and their enhancement of HL-60 leukemia cell differentiation

Abstract: DAAS is the diacetoxy acetal derivative of a-santonin and induces HL-60 cell differentiation into granulocytes. In this report, we investigated the structure-activity relationship (SAR) of DAAS derivatives in the differentiation of human HL-60 leukemia cells. Although its derivatives themselves had less effect on HL-60 cell differentiation than DAAS, the monoacetyl derivative, 2, mainly induced HL-60 cell differentiation. Moreover, compound 2 synergistically enhanced all-trans retinoic acid (ATRA)-induced HL-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…We earlier reported that activity order was DAAS (Diacetyl ) > C 13 -monoacetyl >> C 6 -monoacetly ≈ Diol (1) in DAAS derivatives (Kim et al, 2008a). But in its C 6 -epimer series, activity order showed some different fashion from DAAS.…”
Section: Sar Of C 6 -Epimer Derivatives Of Daas On Hl-60 Cell Differementioning
confidence: 94%
See 1 more Smart Citation
“…We earlier reported that activity order was DAAS (Diacetyl ) > C 13 -monoacetyl >> C 6 -monoacetly ≈ Diol (1) in DAAS derivatives (Kim et al, 2008a). But in its C 6 -epimer series, activity order showed some different fashion from DAAS.…”
Section: Sar Of C 6 -Epimer Derivatives Of Daas On Hl-60 Cell Differementioning
confidence: 94%
“…1), the acetal analogue of α-santonin that contains a non-lactone ring, had remarkable anti-leukemic activities, inducing HL-60 cell differentiation via down-regulation of NF-κB binding activity (Kim et al, 2006a). Also, we have investigated the SAR of DAAS derivatives (Kim et al, 2006b;Kim et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%